A Case-Based Guide to Clinical Endocrinology - Davies, Terry F.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Now in a revised and expanded third edition, this case-based guide emphasizes the latest investigative advances in both imaging and molecular diagnostics and new treatment approaches for a wide variety of common and complex endocrine conditions. Utilizing unique clinical case histories, each main endocrine condition and disorder is curated by a senior Section Editor with an introduction to his or her area covering both physiology and pathophysiology. This introductory chapter is followed by a number of case histories written by invited experts and designed to cover the important relevant pathophysiology, following a consistent chapter format for ease of use, including bulleted objectives, case presentations, review of the diagnosis, lessons learned, and 3-5 multiple-choice review questions. Section headings include the pituitary, thyroid (overactivity, underactivity and cancer) and parathyroid, adrenal disorders, metabolic bone disease, type 2 diabetes, lipid abnormalities, obesity, and pregnancy. Topics new to this edition include PCOS, transgender medicine and the endocrine effects of viral infections. With a focus on covering major parts of the APDEM curriculum, A Case-Based Guide to Clinical Endocrinology remains a tremendous resource for junior and veteran clinicians alike. .
Part I. Pituitary Disorders -- Introduction to Pituitary Disorders -- Pituitary Tumor Behavior and Disease Severity in Patients with Acromegaly -- Abrupt Weight Gain, Hypertension and Severe Hypokalemia in a Young Male -- Dopamine Agonist-Induced Impulse Control Disorders -- Part II. Thyroid Overactivity -- Introduction to Thyroid Overactivity -- Immunoglobin G4 and Grave$1 (Bs Orbitopathy -- Subclinical Hyperthyroidism: Case Report and Review of the Literature -- A Case of Gestational Thyrotoxicosis -- Part III. Thyroid Underactivity -- Introduction to Thyroid Underactivity -- Managing Hypothyroidism: Increasing Levothyroxine Requirements -- Gastrointestinal Disease and Levothyroxine Absorption -- Drug-Induced Central Hypothyroidism -- Part IV. Thyroid Cancer -- Introduction to Thyroid Cancer -- Papillary Thyroid Cancer -- Anaplastic Thyroid Carcinoma -- Medullary Thyroid Carcinoma -- Part V. Adrenal Disorders -- Introduction to Adrenal Disorders -- Adrenal Incidentalomas and Autonomous Cortisol Secretion -- Pheochromocytoma -- Ectopic ACTH Syndrome -- Part VI. Primary Hyperparathyroidism -- Introduction to Primary Hyperparathyroidism -- Cinacalcet Use in Primary Hyperparathyroidism -- A Case of Apparently Sporadic Primary Hyperparathyroidism Carrying a Germline Mutation of CDC73 Gene -- Challenges in the Preoperative Localization of Hyperfunctioning Parathyroid Tissue in a Patient with Primary Hyperparathyroidism -- Part VII. Metabolic Bone Diseases -- Introduction to Metabolic Bone Diseases -- Type 2 Diabetes and Bone -- Hypercalcemia and High Bone Mineral Density -- Rare Presentation of Severe Pediatric Rickets -- Part VIII. Endocrine Disorders in Men -- Introduction to Endocrine Disorders in Men -- Adult Onset Hypogonadism -- Congenital Hypogonadotropic Hypogonadism -- Klinefelter Syndrome -- Part IX. Endocrine Disorders in Pregnancy -- Introduction to Endocrine Disorders in Pregnancy -- Prolactinoma in Pregnancy -- Adrenal Insufficiency in Pregnancy -- Pheochromocytoma in Pregnancy -- Diagnosis and Management of Thyroid Cancer in Pregnant Women -- Part X. Type 2 Diabetes Mellitus -- Introduction to Type 2 Diabetes Mellitus -- Initial Diagnosis and Management of Type 2 Diabetes Mellitus -- Outpatient Management of Type 2 Diabetes Mellitus -- Inpatient Management of Type 2 Diabetes Mellitus -- Part XI. Lipid Abnormalities -- Introduction to Lipid Abnormalities -- A Case of Heterozygous Familial Hypercholesterolemia: Success of Long-term Management -- A 53 Year Old Man with Severe Combined Hyperlipidemia and Multiple Medication Sensitivities -- Familial Partial Lipodystrophy Presenting as Extreme Hypertriglyceridemia and Acute Pancreatitis -- Part XII. Obesity -- Introduction to Obesity -- Obesity Assessment and Management Using an Illustrative Case in Severe Mental Illness -- Obesity Management and Use of Very Low Energy Diets -- Obesity Case Management: Bariatric Surgery -- Part XIII. Polycystic Ovary Syndrome -- Introduction to Polycystic Ovary Syndrome -- PCOS and Hirsuties -- PCOS and Reproduction -- PCOS and Insulin Resistance -- PCOS and the Metabolic Syndrome -- Part XIV. Transgender Medicine -- Introduction to Transgender Medicine -- Trans-Masculine Therapy -- Peri-operative Estrogen Considerations for Transgender Women Undergoing Vaginoplasty -- Feminizing Gender-Affirming Hormone Therapy: Special Considerations for Older Adults -- Part XV. Endocrine Effects in Virus Infections -- Introduction to Endocrine Effects in Virus Infections -- Adrenal Function in HIV Infection -- HIV Infection and Lipodystrophy -- Endocrinopathies of SARS-CoV-2.s
Keywords: Family medicine; Endocrinology; General Practice and Family Medicine; Endocrine System Diseases; Endocrine System -- pathology